A SPECIAL CASE OF CALCULATION OF OPTICAL SYSTEM FOR A COLLIMATOR WITH AN ANFOCAL ACHROMATIC COLLIMATOR: A SPECIAL CASE OF CALCULATION OF OPTICAL SYSTEM FOR A COLLIMATOR WITH AN ANFOCAL ACHROMATIC COLLIMATOR - Zhekov, Zhivko; Kalev, Krasimir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In connection with the development of collimator for the needs of the defense, the research on mirror-lens objectives is being enhanced, especially objectives with an afocal achromatic compensator, located in parallel shaft of light with a reflector in the form of a flat plane.